Ensemble Deep Learning Algorithm for Multi View Image Fusion - Vijendran, Anna Saro; Ramasamy, Kalaivani (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In order to create a synthetic image with more valuable data than just single particular image could ever provide, image fusion attempts to combine many image graphs of the similar subject. The clarity of the majority of original images is restricted by imaging sensors’ limitations and broadband signal transmission. An innovative multi-modality clinical image fusing technique is presented in this study to enhance the image quality and earlier brain tumor detection performance. Hence, ensemble based deep learning algorithm is proposed in this study to increase the Magnetic Resonance Imaging (MRI) brain image fusion performances by minimizing noises, executing segmentations, extracting features, fusing images in primary phases. Initial noise reduction improves image quality. Segmentation process MRI scans divides an image into its parts. Black-and-white images are created. Following that, Lion Swarm Optimization based Convolutional Neural Network (LSOCNN) extracts image characteristics with most information. Eventually, multi-modal image fusion generated lower, intermediate, and upper level images. It can be seen from all angles and fused. To increase image fusion performance, ensemble CNN, DFMI-Net, TA-cGAN algorithms are presented. From the result, proposed ensemble DCNN+DFMI+Cgan compared to previous methods, this approach performs improved in respect of correctness, clarity, memory, and mean square error (MSE).